CHOICE OF EFFECTIVE MEASURES TO PREVENT THE "WAXING" OF PIPES - I. Berdzenishvili; M. Siradze (World Science, 2022)
The article deals with the process of “waxing” of pipes and the choice of effective measures to prevent these negative phenomena. To assess the nature of asphalt-resin-paraffin deposits (ARPD) and select a further investigation scheme, the X-ray Spectral analysis was used. It is shown, that ARPD is a complex system structured by resinous-asphaltene substances and paraffin-naphthenic or paraffin-aromatic hydrocarbons. Mass transfer of solid deposits to the pipe wall is described by the Fick’s differential equation. In order to prevent "waxing" of pipes, compositions of antiadhesive fluorine glass-enamel coatings with a high class of surface cleanliness are proposed.